Strategi Penguatan Industri Halal di Indonesia: Analisis SWOT: Strategy for Strengthening the Halal Industry in Indonesia: SWOT Analysis - Azwar, Azwar; Khaerul Aqbar (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
This research aims to analyze the internal (strengths and weaknesses) and external (opportunities and threats) factors that influence the halal industry in Indonesia and formulate appropriate strengthening strategies based on the results of the SWOT analysis. This research uses a mixed approach, or a combination of qualitative and quantitative methods (mixed method), in the form of an exploratory sequential design using the SWOT analysis technique. The research results show that the strength of Indonesia's halal industry lies in the largest Muslim population in the world, a wealth of natural resources, a strong understanding of Islamic culture, and increased consumer awareness of halal products. However, the halal industry also has weaknesses, such as underdeveloped infrastructure, intense local competition, problems with product quality and authenticity, and difficulties in accessing global markets. From the external side, there are great opportunities to enter international markets, develop innovative halal products, establish strategic partnerships, and take advantage of local market growth. However, the halal industry is also faced with the risk of changing consumer trends, global competition, and product quality problems. Therefore, strengthening strategies are needed in several main areas: increasing productivity and competitiveness, implementing and strengthening policies and regulations, and strengthening finance and infrastructure. Apart from that, efforts are also needed to increase brand awareness of halal products and public awareness about halalness.